PELINGGIH PADMASANA DALAM EKISTENSI AGAMA HINDU (Bentuk dan Makna) - A.A. Pt. Suari; Gede Arya Krishna Duta Putra Tuboeh (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Bali island, is an island famous for its natural beauty, culture, and tradition which is very thick with its traditional nuances. then don't be surprised, if the island of Bali is called